STUDENTS’ PERCEPTIONS ON THE USE OF L1 IN EFL LEARNING - Anindya, Alya Sekar; Inayati, Dian; Ulani, Amidi (LLT Journal: A Journal on Language and Language Teaching, 2022)
The use of first language (L1) in EFL classrooms is considered taboo since it is believed to hinder students’ foreign language (L2) development, while others support it due to its benefits in facilitating students’ access to L2. Hence, this study attempts to investigate students’ perceptions on the use of L1 in EFL classrooms. In this qualitative study, the data were collected through observations and interviews with three selective respondents. The findings reveal the students’ positive perception on the use of L1 in their EFL learning. Mediated by L1, the students were able to understand and engage well to EFL learning, which they believe would help shape and develop their English. Despite the benefits, they agree on some restrictions made by EFL teachers to provide opportunities for students to practice their English. Some suggestions for EFL teachers are postulated.